Measurement of Market Integration and Arbitrage - Chen, Zhiwu; Knez, Peter J. (Review of Financial Studies, 1995)
We develop a measurement theory of market integration, based on two notions of “integrated markets”. First, two markets cannot be perfectly integrated in any sense if one can construct two portfolios, one from each market, that have identical payoffs but different prices. In that case, the law of one price is violated across the markets. Second, they cannot be integrated in a stronger sense if there are cross-market arbitrage opportunities. Two measures of market integration are developed, respectively reflecting these notions. The smaller the measures, the more closely integrated (in the respective senses) the markets. Among other things, they are interpreted as measuring pricing discrepancy between markets.